2017
DOI: 10.1016/j.jtcvs.2017.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Young infants with severe tetralogy of Fallot: Early primary surgery versus transcatheter palliation

Abstract: Early primary repair for neonates may increase surgical reoperation, whereas transcatheter palliation comes at a cost of increased catheter reintervention. However, overall outcomes between groups, in terms of survival, growth, and hemodynamic parameters, were comparable, suggesting that both strategies are a reasonable option for children with severe tetralogy of Fallot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 26 publications
4
35
0
1
Order By: Relevance
“…Using a palliation method to allow for more somatic growth appears to be a preferable option, as both palliation methods appear to be comparable to PrR in these patients. Our finding, that using a transannular patch is associated with both increased mortality and future need for PVR, supports other data suggesting that a key aspect of repair is preserving the pulmonary valve when possible 5. It is reassuring that reinterventions in the first 10 years after ToF repair are not associated with increased mortality, only with further subsequent reinterventions.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Using a palliation method to allow for more somatic growth appears to be a preferable option, as both palliation methods appear to be comparable to PrR in these patients. Our finding, that using a transannular patch is associated with both increased mortality and future need for PVR, supports other data suggesting that a key aspect of repair is preserving the pulmonary valve when possible 5. It is reassuring that reinterventions in the first 10 years after ToF repair are not associated with increased mortality, only with further subsequent reinterventions.…”
Section: Discussionsupporting
confidence: 88%
“…Previous reports described a high incidence of PA reinterventions after RVOTd 5. After matching we found similar PA reintervention rates in all three groups.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In this study, neonatal repair was independently associated with longer THD. Other studies have shown that neonatal repair for TOF is associated with increased circulatory support time, length of mechanical ventilation, greater use of postoperative inotropes, longer LOHS, and subsequent reoperations . The neonatal heart might be less “mature” and more vulnerable in the symptomatic neonate with TOF and thus less able to tolerate exposures such as cardiopulmonary bypass and ventriculotomy during surgical repair.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that neonatal repair for TOF is associated with increased circulatory support time, length of mechanical ventilation, greater use of postoperative inotropes, longer LOHS, and subsequent reoperations. 15,22,27,29,30 The neonatal heart might be less "mature" and more vulnerable in the symptomatic neonate with TOF and thus less able to tolerate exposures such as cardiopulmonary bypass and ventriculotomy during surgical repair. Neurologic vulnerability of the neonate as compared to infant may also be an important variable in this decision, but a variable that has not been fully addressed.…”
Section: Discussionmentioning
confidence: 99%